Comparative biodiversity and effect of different media on growth and astaxanthin content of nine geographical strains of Haematococcus pluvialis - Noroozi, Mostafa; Omar, Hishamuddin; Napis, Suhaimi; Hejazi, Mohammad Amin; Tan, Soon Guan (Academic Journals, 2012)
Haematococcus pluvialis is a unicellular green volvocale alga living in temporary shallow freshwater ponds. It has many applications for humans, poultry and fishes due to its ability to produce astaxanthin. The main objective of this study was to evaluate the biodiversity and growth of nine strains of H. pluvialis originating from three countries: Iran, USA and Finland in distinct growth media (Bold, NIES, OHM, Mixotroph and COMBO) and their molecular marker investigation. The biomass, astaxanthin and chlorophyll concentration were determined in all strains. The results of this study showed that Mixotroph growth medium produced the highest biomass of 0.577 g dry weight/l followed by COMBO and OHM media, respectively. However, the highest astaxanthin concentration was obtained from COMBO and OHM growth media and Iran4 and USA3 strains. Hence, the Mixotroph is suitable for biomass production and OHM or COMBO is appropriate for astaxanthin production; so two steps cultivation is feasible to produce astaxanthin. The results depicted geographical differentiations of the strains with Iran4 and USA2 strains producing the highest biomass and Finland2 strain showing the slowest one. The inter-simple sequence repeat (ISSR) and random amplified polymorphic DNA (RAPD) molecular markers were used as suitable tools for the purpose of finding out genetic variations and genetic discrimination of H. pluvialis strains. This technique differentiated the strains based on their geographical status.